Earnings management using "Carryovers": Accounting practices in Toshiba's Visual Products business. (September 2022) - Gujarathi, Mahendra R.; Dugar, Amitabh; Ruff, Michael F.
Abstract: This case helps you to apply the concept of accrual accounting to a real-world situation and to understand the intertemporal effects of accruals on financial statements. It helps you to understand the importance of recording the economic substance of transactions rather than their mere form. In analyzing the case, you develop skills to research FASB Codification, identify applicable accounting standards, and use them to make professional judgments. You need to determine whether Toshiba's accounting treatment is conceptually sound and whether it represents a faithful depiction of the Company's economic reality. The case assignment improves your ability to think critically, work in groups, reach rational conclusions, and convincingly communicate them.